Pengaruh Lama Fermentasi Terhadap Karakteristik Minuman Probiotik Sari Buah Nanas (Ananas comosus L.) dengan Isolat Lactobacillus rhamnosus SKG34 - Fernando Pangaribuan, Jimmy; Nocianitri, Komang Ayu; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aims to determine the effect of fermentation time on the characteristics of pineapple probiotic juice with Lactobacillus rhamnosus SKG34 isolate and determine the appropriate fermentation time to produce the best probiotic pineapple juice characteristics. This study used a Completely Randomized Design (CRD) with treatment duration of fermentation, namely 0 hours, 12 hours, 24 hours, 36 hours and 48 hours. Each treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by analyse of variance and if the treatment had a significant effect, then continued with the Duncan Multiple Range Test (DMRT). The results showed that the duration of fermentation affected the total sugar, total acid, acidity (pH), color hedonic, aroma hedonic, taste hedonic, sour and sweet taste scoring, and overall acceptance, but had no effect on total LAB. The 24-hour fermentation treatment resulted in the best characteristic of probiotic pineapple juice with total LAB 9.8 x 10 9 CFU/ml, total sugar 13.81%, total acid 0.54%, pH 3.47, liked color, aroma liked, slightly sour and slightly sweet flavors were liked, and overall acceptance was liked.